There's an App for That: The Development of an NFL Team Mobile Application - Greg Greenhalgh; Brendan Dwyer; Brian Biggio (Journal of Applied Sports Management, 2014)
Technological advances, such as mobile applications (apps) are enhancing the way many sport fans interact with their favorite teams. Many sport organizations have started to utilize mobile apps in an effort enhance fans' experience at the stadium and abroad. The current case study examines the adoption of a mobile app by a NFL team. The adoption of innovation framework provided by Hoeber and Hoeber (2012) was used to guide seven interviews with key decision-makers within the NFL team, with findings overlaid on the three stages and three determinants of innovation adoption. Findings revealed the team's need to interact with fans and enhance the game day experience were primary environmental determinants for the adoption of this innovation. Furthermore, the shift in leadership's attitude toward innovation was a significant managerial determinant. The qualitative results provide a rich description of the innovative process.
Keywords: NFL; mobile app; adoption of innovation; qualitative